1996
DOI: 10.1007/bf02508640
|View full text |Cite
|
Sign up to set email alerts
|

Heated oyster shell-seaweed calcium (AAA Ca) on osteoporosis

Abstract: A randomized, prospective, double-blind test was carried out to compare the effects of heated oyster shell-seaweed calcium (AAA Ca), calcium carbonate, and placebo in 58 elderly, hospitalized women with the mean age of 80 divided into three groups. Group A received 900 mg/day Ca as AAA Ca, Group B 900 mg/day Ca as CaCO3, and Group C placebo besides regular hospital diet containing approximately 600 mg Ca/day for 24 months. From the 25th to the 30th month, all groups were given AAA Ca. Lumbar spine and radial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The same amount of calcium provided by calcium carbonate had no significant effect in comparison with placebo (Fujita et al, 1996). To our knowledge, there are only a few clinical trials published in this field.…”
Section: Seaweeds and Osteoporosis: Clinical Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…The same amount of calcium provided by calcium carbonate had no significant effect in comparison with placebo (Fujita et al, 1996). To our knowledge, there are only a few clinical trials published in this field.…”
Section: Seaweeds and Osteoporosis: Clinical Studiesmentioning
confidence: 85%
“…To our knowledge, there are only a few clinical trials published in this field. These effects were paralleled with a lower urinary calcium excretion (Fujita et al, 1996) and a decrease in bone degradation markers (Ohgitani et al, 1997). In a double-blind cross-over trial, a preparation of calcium from oyster shell and heated seaweed extract (Cystophyllum fusiforme), providing 900-mg Ca per day, was shown to increase lumbar spine bone density of 58-year-old postmenopausal women after 6 and 24 months of supplementation, when compared to placebo.…”
Section: Seaweeds and Osteoporosis: Clinical Studiesmentioning
confidence: 96%
“…Heated seaweed extract from Cystophyllum fusiforme proved effective in increasing BMD when added to active absorbable calcium from oyster shell powder in a range of populations with osteoporosis/osteopenia or at high risk of these conditions ( n = 137, n = 58, and n = 34 subjects) . Similarly, a mineralized seaweed product extracted from the red algae Lithothamnion calcareum exhibited beneficial effects in osteoarthritic patients, who reported decreased joint pain and increased mobility after supplementation ( n = 70 and 29 subjects) .…”
Section: Bone Healthmentioning
confidence: 98%
“…Though they did find that individuals with higher reported calcium intake had a lower risk of osteoporosis and osteopenia, they did not elaborate on the source of calcium in the diet, which could have been from seaweed consumption. Despite these findings, several intervention studies utilizing different species of seaweed have reported beneficial effects on markers of osteoporosis such as BMD, pain, and joint mobility, measured using Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, 6‐min walking distance, and range‐of‐motion assessments along with the comprehensive arthritis test …”
Section: Bone Healthmentioning
confidence: 99%
“…In the Katsuragi Calcium study, a prospective, randomized, double blind and placebo-controlled study compared the effect of AAACa on osteoporosis with that of CaCO 3 in hospitalized women with a mean age of 80 years. It was found that AAACa alone increased spinal bone mineral density significantly over the level in subjects given a placebo, whereas CaCO 3 did not [2,3]. Fracture occurrence over the two year test period from among 58 subjects was 0 of 5 in the AAACa Group, 2 of 7 in the CaCO 3 Group and 3 of 5 in the Placebo Group, on evaluation of all X-rays available at the beginning and end of the test period.…”
Section: Introductionmentioning
confidence: 99%